Impact of the Covid-19 pandemic on the global role of the US - Jelica Gordanić (Međunarodni Problemi)
Even before the COVID-19 pandemic, Trump’s politics of unilateralism had cast a shadow on the global role and leadership of the US. The COVID-19 pandemic is the first global crisis since the Cold War in which the US has not led the global response. On the other hand, global actors, like China and Russia, have been using the pandemic as a strategic opportunity. Medical supply donations and vaccine diplomacy have become very important tools for China and Russia to improve their global role and influence. These states have enlarged their influence in the Balkans, Latin America, Africa, Asia, and the Pacific region and improved their position as global actors. The paper examines why the US lost its global role during the pandemic and what the Biden administration can do to regain global leadership. The author considers that Trump’s handling of the pandemic has created division and confusion rather than an effective strategy on a national and global level. The author concludes that embracing the multilateralism of the Biden administration is a necessary step forward. Rejoining the WHO, cooperating with COVAX and Gavi, and forming the Quad Vaccine Partnership may be the best strategies for the United States to reclaim its global role and leadership in the face of the COVID-19 pandemic.